The Marrakesh Treaty and Facilitating Access to Literary Works in the Field of Knowledge for Blind People - Rroisah, Kholis; Rakhmi, Wendy Budiati (Hasanuddin Law Review, 2018)
Freedom to gain knowledge, information and technology is very important by everyone including blind people which one realized the right of access to literary works through the Marrakesh Treaty 2013. Regulation about facilitating access to copyright of published works for blind people in Indonesia is still considered inadequate to give protection in the implementation of freedom to gain knowledge. This study applied normative juridical approach described descriptive-analytically. Accessibility to the scientific work of the blind people is a part of human rights which must be respected, protected and fulfilled by the State. The Government has an important role in the realization of the wider access of the disabled by formalizing the governmental regulation in accordance with the mandate of Article 44 paragraph (4) of the Copyright Act 2014 and the Government shall immediately establish The Disabilities National Commission granted the authority and responsibility to fulfill the facilitation of access for blind people and limited reading by guiding Marrakesh Treaty or by looking at other country's regulatory practices.